2017
DOI: 10.1038/s41598-017-04125-6
|View full text |Cite
|
Sign up to set email alerts
|

Development of lysosome-mimicking vesicles to study the effect of abnormal accumulation of sphingosine on membrane properties

Abstract: Synthetic systems are widely used to unveil the molecular mechanisms of complex cellular events. Artificial membranes are key examples of models employed to address lipid-lipid and lipid-protein interactions. In this work, we developed a new synthetic system that more closely resembles the lysosome – the lysosome-mimicking vesicles (LMVs) – displaying stable acid-to-neutral pH gradient across the membrane. To evaluate the advantages of this synthetic system, we assessed the distinct effects of sphingosine (Sph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 52 publications
(86 reference statements)
0
30
0
Order By: Relevance
“…Several studies have addressed the effect of SO on bilayer membranes and its ability to change membrane biophysical properties, by promoting changes in fluidity [92][93][94]97,[100][101][102], domain formation [101,103] or membrane permeability [94,102,104,105] (Fig. 4).…”
Section: Effect Of So On the Biophysical Properties Of Membranesmentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies have addressed the effect of SO on bilayer membranes and its ability to change membrane biophysical properties, by promoting changes in fluidity [92][93][94]97,[100][101][102], domain formation [101,103] or membrane permeability [94,102,104,105] (Fig. 4).…”
Section: Effect Of So On the Biophysical Properties Of Membranesmentioning
confidence: 99%
“…The impact of SO on membrane structure, thermotropic behavior and lipid phase separation, can have consequences on membrane permeability, both in model and cell membranes [94,102,104,105]. Changes in membrane permeability might derive from i) structural defects created by SO as a consequence of lipid phase separation into rigid and fluid lamellar phases [94,105]; ii) the formation of small short-lived channels that allow the passage of small molecules and ions [104]; and iii) non-lamellar structures formed upon interaction of SO with negatively charged lipids [102]. Additionally, it was shown that SO-induced membrane permeability depends on pH and membrane lipid composition: SO promotes a rapid increase in membrane permeability in conditions mimicking the lysosome pH environment, i.e., with internal acidic and external neutral pH.…”
Section: Effect Of So On the Biophysical Properties Of Membranesmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, the effect of pH on the structure of lipid bilayers has been less examined leading to a poor understanding of this effect at a molecular level. Yet pHinduced changes in membranes play a critical role in many biological processes including the stability and integrity of the lysosomal membranes (Carreira et al 2017), the formation of cholesterol-enriched domains (Redfern and Gericke 2005) and drug partitioning (Krämer et al 1998;Schaper et al 2001). Our understanding of pH on biological membranes is also important to comprehending systemic health issues such as inflammation (Kellum et al 2004), tumour growth (Gerweck and Seetharaman 1996;Kato et al 2013), ischaemic stroke (Huang and McNamara 2004) and epileptic seizures (Ziemann et al 2008).…”
Section: Introductionmentioning
confidence: 99%